Elementary characterization of metals in lipsticks by EDXRF - Catarina Alzira Montenegro Peddis Torres; Sergei Anatolyevich Paschuk; Danielle Cristine Narloch; Janine Nicolosi Corrêa (Brazilian Journal of Radiation Sciences)
Usually classified as cosmetic consumer products, makeups usually contain significant quantities of colorants, which may contain toxic and heavy metals, such as Hg, Cd, As, Cr, Tl, and Pb. According the Health Regulatory Agency (ANVISA), lipsticks are classified as low health risk, grade 1. However, similar makeups for the children are classified as grade 2, high risk, and within this category there is no cosmetic product for embellishment. Many metals, present in the colorants, can cross the mucous membranes and skin barrier and could be absorbed into the blood system, which can cause systemic damage to internal organs. Many chemical components present in the lipsticks, such as Al, Pb, Cd, Br, Cu, Zr, Cr, Hg, TiO2 in nanoparticulate form, could be considered as potentially toxic. Present work was undertaken in order to study the presence of mentioned above metals in the samples of commercial lipsticks. The metals characterization and elementary identification was performed using EDXRF technique. This method allows to perform the qualitative and quantitative analysis by means of the characteristic X-rays spectra emitted by the elements present in studied samples. The experimental setup was based on mini X-ray tube with Ag target and detector (AMPTEK). The partial results of the study revealed that the lipstick samples revealed the presence of Mg, Al, Si, P, S, Cl, K, Ca, Ti, Cr, Mn, Fe, Ni, Zn, Br, Rb, which suggest that prolonged and constant use of such cosmetics may constitute a potential threat to the health especially in the case of children.